Faith and reason through Christian history : a theological essay - Kaplan, Grant (The Catholic University of America Press, 2022)
"It is impossible to understand the history of Christian theology without taking into account the relationship between faith and reason. Many works give an overview of faith and reason, or outline key principles, while others put forward a thesis about how one should understand the relationship between faith and reason. In this theological essay, Grant Kaplan revisits the key figures and debates that shape how faith and reason relate. Divided into three parts, Kaplan invites readers into a conversation rather than a drive-by. Readers will encounter the words and arguments of some of Christianity’s greatest thinkers, some well-known (Augustine, Aquinas, Newman) and others nearly forgotten. Readings of these figures bring them to life in an accessible manner. In Faith and Reason through Christian History, the roughly fifty figures treated are given sufficient room to breathe. Rather than simply summarizing their thought, Kaplan traces their arguments through key texts. This book will appeal to a range of audiences: theologians and philosophers, instructors, graduate students, seminarians, lay study groups, and undergraduate theology majors. No book today accomplishes what this book does!" --